FORMATION OF ECONOMIC COMPETENCE OF PRESCHOOL EDUCATION LEADERS IN THE PROCESS OF PROFESSIONAL DEVELOPMENT: INTERPRETATION OF PROBLEMS AND SOLUTIONS - Nigmаtоvа Gulnоrа Nurxаnbеtоvnа (Web of Journals Publishing, 2024)
The economic competence of leaders within preschool education organizations is pivotal for the efficient management and sustainability of early childhood education institutions. This paper explores strategies to enhance the economic competence of preschool education organization leaders through professional development programs. Key strategies include financial management workshops focusing on budgeting, resource allocation, and financial planning tailored to the specific needs of preschool education organizations. Additionally, leaders should be educated on understanding various funding sources, cost management, revenue generation, and data analysis skills. Legal and regulatory compliance, strategic planning, and networking opportunities are also essential components of professional development programs aimed at enhancing economic competence. By implementing these strategies, preschool education organization leaders can build the necessary economic competence to ensure the financial sustainability and success of their institutions.
Keywords: Financial Management, Budgeting, Resource Allocation, Funding Sources, Government Grants, Private Funding, Tuition Fees, Cost Management, Revenue Generation, Fundraising, Fee Structuring, Partnerships, Data Analysis, Financial Data, Trends Analysis, Forecasting, Financial Sustainability.